A COMPARATIVE STUDY BETWEEN HEPARIN AND ENOXIPARIN EFFECTIVENESS IN PATIENTS WITH TOTAL KNEE REPLACEMENT IN PREVENTING DEEP-VEIN THROMBOSIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Background Several recent studies have demonstrated that the prevalence of deep-vein thrombosis after total knee arthroplasty in the eastern population is similar to that in the Western population (1, 2). However,the locations of the thromboses in the patients have differed,with a predominance of distal clots (in the calf) and very few proximal clots (in the thigh or pelvis) or pulmonary emboli. PATIENTS AND METHODS This was a prospective randomized controlled clinical trial conducted from August 2010 through August 2011 at the orthopedic department of Nursing Home Hospital, Baghdad Medical City, on patients undergoing primary elective knee arthroplasty. Fifty-eight (58) patients (23 women and 35 men) scheduled to undergo total knee replacement were selected. Patients range in age (43-71 years), weight (60-113) kg, height (145-181 cm), and BMI (19.84-38.45 kg/m²). RESULTS The patients who participated in this study were 36 males (64.3%) with a mean age of 53.8± 12.5 years and a mean body mass index (BMI) of 28.7 ± 5.2 kg/m2, and 20 females (35.7%) with a mean age of 51.5±9.1 years and a mean BMI of 29.85±5.1 kg/m2. The association between enoxaparin use and a reduction in the incidence of DVT is highly significant at a P value ≤ 0.01. There is no statistically significant association between DVT development and BMI, age, site of operation, or sex distribution. Preoperative ultrasonography clarified that the overall prevalence of asymptomatic DVT was 3.45%, with 2 of 58 patients with asymptomatic DVT in the calf (they had been excluded from our study). For the remaining 56 patients (in both groups), there were 31 operations on the left side and 25 on the right side. Conclusions: . DVT is one of the most common and serious medical conditions that occur after being hospitalized for a serious illness or undergoing major surgery. Enoxparin is effective in preventing DVT after total knee arthroplasty. The incidence of DVT is not associated with age,sex, BMI, or site of operation in both males and females. The DVT occurs in the calf veins... The bedside diagnosis of venous thrombosis is insensitive and inaccurate, and the absence of these symptoms and signs doesn’t exclude DVT in patients with total knee replacement. Doppler sensitivity is 85% and accuracy is 96.